Three dimensional finite element analysis of the influence of the umbrella arch on the settlements induced by shallow tunneling. (June 2019) - Hounyevou Klotoé, C.; Bourgeois, E.
Abstract: This paper presents an analysis of the influence of the umbrella arch on the settlements induced by shallow tunneling, based on three-dimensional finite element simulations using CESAR-LCPC. The approach takes into account the actual geometry of the umbrella arch and the lining, and the various aspects of staged construction, notably the cycle of installation of the pipes. The results show that the influence of the umbrella arch on the settlements remains modest, at least for the range of parameters adopted in this study. Also, the results show that the numerical analysis can be carried out with a simplified geometry.